International entrepreneurship and the development of competencies in family businesses: Case study - Noronha, Matheus Eurico Soares de; Isaac, Victor Ragazzi; de Souza Vieira Silva, Rosemeire; Moraes, Lucas Marques (Journal of Sustainable Competitive Intelligence, 2024)
Purpose: Explain how the main competencies developed by a family business in an emerging market help to reach international markets. Methodology/approach: A qualitative research was conducted with family members who participated in the expansion process, showing that the members' family organization is essential to develop each of the competencies during the internationalization process. Originality/Relevance: Theoretical and managerial contributions are presented, as it adds new discoveries to the international business literature, focusing on companies from emerging markets that internationalize to developed markets. Key findings: The results show that the internationalization of the business to Portugal occurred by the partners, who tend to centralize the business management decision-making processes. The knowledge acquired in Brazil improved the internationalization process and the establishment of the brand in Portugal. Theoretical/methodological contributions: The study contributes to research on internationalization of family businesses, demonstrating that the creation of competencies oriented to entrepreneurial emerging markets is fundamental for the strategic development of this type of company in its process of internationalization. The research presents an empirical report of international entrepreneurship from qualitative emerging markets.